Characterization of ambient aerosols in Northern Thailand and their probable sources - Tippayawong N. (2014)
The present study examines variation of ambient aerosol mass and number concentrations in Chiang Mai, Thailand during winter. Aerosol particle samples were collected and measured at four different sites, representative of urban, industrial, residential and rural areas during daytime between December 2003 and January 2004. Average 10 h particulate matter (PM) mass concentrations were found to be in the range of 75-290 μg/m3, with average value of 149 ± 45 μg/m3. Urban and industrial areas appeared to have higher PM loading than residential and rural areas. Number concentration and size distribution of particles in the range of 0.3-10.0 μm did not exhibit any marked variation between sites. Relatively stable number concentrations were reported. Temporal variation of number concentrations was not clearly significant. No short term peak observed during rush hours. During sampling period, the average number concentration for 0.3-0.5, 0.5-1.0, 1.0-5.0 and 5.0-10.0 μm were 6.60 × 106, 1.18 × 106, 2.11 × 105 and 1.12 × 104/m3, respectively. Particles with diameter smaller than 1.0 μm accounted for over 90 % of the total number concentration. Concentrations of major metals were determined by atomic absorption spectrophotometer (Pb, Fe, Al, Si, Cr, Cd, Ni, Zn) and flame photometer (K, Na and Ca). Data obtained were used to identify probable sources via a multivariate analysis. Si, Na, Fe, Ca, Al and K were the six dominant elements in the airborne PM. Principle component analysis was carried out and major sources of airborne PM in Chiang Mai were determined, namely, (1) long distance sources such as sea spray, earth soil and industrial combustion, (2) short-distance sources such as crustal re-suspension, vehicular related emissions and vegetation burning, and (3) the unknown distance sources with low influence of traffic emissions. © Autumn 2006, IRSEN, CEERS, IAU.